THE EFFECT OF LIGHT COLOR VARIATION IN SIMPLE LIGHT TRAPS ON THE NUMBER OF FRUIT FLIES (BACTROCERA SP.) - Sobiatin, Eka; Herianto, Herianto; Khosiyatun, Nur; Kuswanto, Heru (Universitas Muhammadiyah Yogyakarta, 2019)
Fruit flies (Bactrocera sp.) are the most common types of plant pests attacking fruit plants. The pest attacks the fruit in the plantation. The control of fruit flies is quite difficult, which is usually done by using eugenol. Fruit flies are insects that are sensitive to light with wavelengths of 300-650 nm. The light trap is a method commonly used yet it is rarely used to control the fruit flies. This research was conducted to determine the effect of the color variation in light traps on the number of trapped fruit flies. This study used quasi-experimental research methods. The data were analyzed descriptively and continued with one-way ANOVA statistical testing using SPSS 25.0. The results showed that the highest average number of fruit flies was in light traps with the addition of blue lights of 17.22. Post hoc tests showed that blue lights were more effective in attracting flies into light traps.